PERANAN BADAN PERENCANAAN PEMBANGUNAN DAERAH DALAM PENYUSUNAN RENCANA PEMBANGUNAN JANGKA MENENGAH DAERAH KABUPATEN HALMAHERA BARAT - Mangar, Jembris; Mandey, Jantje; Kiyai, Burhanuddin (JURNAL ADMINISTRASI PUBLIK, 2016)
Abstract:This study aims to determine the role of the Regional Planning Board in the preparation of medium-term development plan West Halmahera. To answer the research problem, then apply the descriptive method with qualitative approach, then seven (7) the informant set as a reference in the collection of data or information by interviewing one by one starting from the element of Regional Development Planning Board as many as five people, and two people from the Budget Team Local government (TAPD), then the data was analyzed using qualitative analysis techniques interactive model of Miles and Hubernann.Based on the research results indicate that the role of BAPPEDA Halmahera can be seen from (1) Preparation of a preliminary draft RPJMD. (2) Preparation of a draft strategic plan on education. (3) The drafting of RPJMD. (4) Council planning (Musrenbang) medium term. (5) Preparation of the final draft RPJMD. (6) Determination of local regulation on RPJMDReferring to some of the findings in this study, it is necessary to provide some suggestions as solutions to problems in this study, as follows: (1) Implementation of the good and the right of each stage of the preparation RPJMD (2) an increase in the number of qualified human resources and improve the quality existing human resources as well.Keywords: Role BAPPEDA in the preparation of medium-term development plan